Strength training in pregnancy. Systematic review of benefits and risks - Demel, Karol; Kantor, Antoni; Król, Jakub; Bialic, Łukasz; Dziedzic, Monika; Polok, Sebastian; Potoczek, Adriana; Talaska, Justyna; Godyń, Marta; Zatłoka-Mazur, Dorota (Quality in Sport, 2025)
Background Strength training during pregnancy has historically been approached with caution, but recent evidence suggests it can be safe and beneficial when properly supervised. This review examines its impact on maternal and fetal health, addressing both advantages and potential risks. Purpose of Research The study aims to evaluate the benefits and risks of strength training during pregnancy, focusing on maternal and fetal outcomes. Research Materials and Methods Data were collected from PubMed, MEDLINE, and Web of Science using keywords like "strength training," "pregnancy," and "maternal health." Guidelines from ACOG and RCOG were analyzed to provide evidence-based recommendations. Basic Results Strength training, when properly supervised, improves musculoskeletal health, reduces gestational diabetes risk, enhances cardiovascular fitness, and supports mental well-being. It may also promote healthier fetal outcomes by regulating maternal blood sugar levels. Risks include overheating, injury, and strain, particularly in cases of pre-existing conditions or improper exercise execution. Conclusions Individualized assessment and tailored programs are essential to maximize benefits and minimize risks. Safe practices, including professional consultation, appropriate exercise selection, and monitoring of intensity, are crucial. Further research is needed to refine guidelines and explore long-term effects. Strength training is a valuable component of prenatal care when conducted safely.